Hubungan Self-Control dan Loneliness dengan Nomophobia Pada Remaja - Syamsul Falah; Sang Ayu Made Adyani (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2026)
Background: Nomophobia is a feeling of inability to be separated from and anxiety when being away from or unable to see a smartphone. Self-control and loneliness are factors that contribute to nomophobia among adolescents. Good self-control and low levels of loneliness can help adolescents avoid severe nomophobia.Purpose: This study aimed to determine the relationship between self-control and loneliness with nomophobia among adolescents at SMAN 1 Sagaranten.Methods: This study employed an analytic design with a cross-sectional approach. The sampling technique used was stratified random sampling, involving a total sample of 275 respondents. The instruments used in this study were the BSCS (Brief Self-Control Scale), UCLA (University of California, Los Angeles), and NMP-Q (Nomophobia Questionnaire) questionnaires. Data were analyzed using univariate and bivariate analyses.Result : The results of the Spearman correlation test showed a significant relationship between self-control and nomophobia p-value = 0.000, with a correlation coefficient of r= -0.421. in addition, loneliness was significantly associated with nomophobia p-value = 0.001, with a correlation coefficient of r = 0.206.Conclusion: This study has implications for health promotion related to self-control, loneliness, and nomophobia. Parents are encouraged to more closely monitor adolescents’ smartphone use intensity and provide education regarding the consequences of behavioral choices, so that adolescents are able to adapt appropriately and avoid risky behaviors such as nomophobia.